2020
DOI: 10.1088/1755-1315/591/1/012033
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid content of five accessions red fruit (Pandanus conoideus Lam.) oil

Abstract: Red fruit (Pandanus conoideus Lam.) is a plant native to Papua, Indonesia. The extracted oil of red fruit has been known to possess potential medical properties, including anti-inflammatory, anti-tumor, and anti-diabetic. The natural antioxidant content such as carotenoids, α-tocopherol, and unsaturated fatty acids are considered to contribute to its bioactivity. In this study, five clonehjnms of red fruit, namely Maler, Bergum, Wesi, Uaghelu, and Kenen, from different regions in Papua, were collected. Caroten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Table II summarizes the potential anti-pigmentation role of carotenoids in red fruit. Red fruit oil (RFO) has high carotenoid and tocopherol contents ( 42 , 91 , 92 ). Roreng et al ( 92 ) showed that carotenoids (pro-vitamin A) in red fruit extracts have high bioavailability.…”
Section: Carotenoid Content In Red Fruit and Its Potential Role As An...mentioning
confidence: 99%
See 2 more Smart Citations
“…Table II summarizes the potential anti-pigmentation role of carotenoids in red fruit. Red fruit oil (RFO) has high carotenoid and tocopherol contents ( 42 , 91 , 92 ). Roreng et al ( 92 ) showed that carotenoids (pro-vitamin A) in red fruit extracts have high bioavailability.…”
Section: Carotenoid Content In Red Fruit and Its Potential Role As An...mentioning
confidence: 99%
“…Wulansari et al ( 91 ) showed that the bioactivity of red fruit is influenced by its natural antioxidant content, including carotenoids, α-tocopherol and unsaturated fatty acids. The aforementioned study involved the collection of five distinct cultivars of red fruit, specifically Maler, Bergum, Wesi, Uaghelu and Kenen, originating from various places in Papua.…”
Section: Carotenoid Content In Red Fruit and Its Potential Role As An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Buah merah contains high levels of carotenoid and flavonoid metabolites. Buah merah ( Pandanus conoideus Lamk) has been reported to have antioxidant, antitumor, immunomodulatory, antiparasitic, and anti-HIV effects [ 6 – 9 ]. As buah merah has good antiparasitic and anti-HIV potential, suggesting potential activity against the SARS-CoV-2 main protease [ 3 ].…”
Section: Introductionmentioning
confidence: 99%